The Impact of Personal, Environmental, and Information Platform Factors on Disaster Information Sharing on Twitter - Amriza, Rona Nisa Sofia; Ngafidin, Khairun Nisa Meiah; Ratnasari, Wiwit (Register: Jurnal Ilmiah Teknologi Sistem Informasi, 2022)
Twitter has become a major platform for disseminating disaster news, providing people with disaster information quickly and precisely. A lot of essential and valuable information can be obtained from this online platform. Twitter users might be able to help with warnings and submit specific and accurate information in a disaster situation. This research attempts to examine factors that affect disaster information-sharing behavior. Furthermore, this study aims to integrate personal, environmental, and information platform factors to gain more insight into the factors influencing Twitter users' willingness to share disaster information. The hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The result showed that Altruism, Self-efficacy, Community Identity, and Information Platforms significantly influence people's decisions to share disaster information on Twitter.